2020
DOI: 10.1108/et-10-2019-0233
|View full text |Cite
|
Sign up to set email alerts
|

Students' perceptions regarding classroom attendance and its impact on their academic performance: evidence from a developing country

Abstract: PurposeThe purposes of this study are to identify the reasons that prevent students from attending lectures, to examine the impact of absenteeism on their academic performance and to explore the role of gender in their attendance.Design/methodology/approachA questionnaire survey made up of statements was distributed to accounting students. Descriptive measures, a five-point Likert scale, Pearson's chi-square test and phi test were employed to achieve the study's objectives.FindingsThe study shows that most of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
2
6
0
1
Order By: Relevance
“…The result indicate that the most significant predictor variables are gender and prior accounting knowledge (p=0.001), and accounting anxiety (p<0.05). The result shows that gender is a predictor of academic performance, consistent with Koh and Koh (1999), Alfan and Othman (2005), Guney (2009), van Wyk (2011), Jansen and de Villiers ( 2015) and Almutawa and Suwaidan (2020); but inconsistent to Brook and Roberts (2021). Indeed, prior literature has indicated that female students are more academically diligent than their male counterpart is.…”
Section: Regression Analysissupporting
confidence: 53%
See 2 more Smart Citations
“…The result indicate that the most significant predictor variables are gender and prior accounting knowledge (p=0.001), and accounting anxiety (p<0.05). The result shows that gender is a predictor of academic performance, consistent with Koh and Koh (1999), Alfan and Othman (2005), Guney (2009), van Wyk (2011), Jansen and de Villiers ( 2015) and Almutawa and Suwaidan (2020); but inconsistent to Brook and Roberts (2021). Indeed, prior literature has indicated that female students are more academically diligent than their male counterpart is.…”
Section: Regression Analysissupporting
confidence: 53%
“…Future research could introduce other determinants such as absenteeism or class attendance. Previous literature discovered that absenteeism is a factor that negatively affects the students' academic performance (Almutawa & Suwaidan, 2020), which means that a student who is absent frequently will not perform well in accounting.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sebanyak 68% responden menyatakan bahwa aplikasi yang digunakan selama pembelajaran jarak jauh mudah digunakan dan dipahami, namun hanya 17% responden yang menyatakan bahwa belajar secara elearning mampu meningkatkan kemampuan mereka dalam memecahkan masalah terkait akuntansi. Permasalahan yang timbul dalam pembelajaran jarak jauh, khususnya pada mata kuliah akuntansi antara lain kinerja siswa dalam belajar akuntansi memiliki hubungan dengan frekuensi kehadiran [2], kecurangan mahasiswa dalam pengerjaan tugas akan meningkat jika tidak ada perubahan dalam metode assessment-nya dari metode yang diterapkan saat tatap muka [1].…”
Section: Pendahuluanunclassified
“…But to establish a relationship between attendance and performance, it is necessary to control other effects, such as gender, quality of teaching, and environmental variables (Sund & Bignoux, 2018). Regarding gender, previous research found that females perform better than males (McNabb et al, 2002;Richardson & Woodley, 2003;Voyer & Voyer, 2014;Almutawa & Suwaidan, 2020), although Lumsden & Scott (1987) found that variations occur depending on the type of assessment and that females perform better than males in coursework, whereas males perform better than females in exams. Furthermore, Cortright et al (2011) found that the influence of regular attendance on examination performance is more important for female students than for male students.…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%